Efforts to Improve Mathematics Learning Achievement Through the Make A Match Learning Model in Class III Students of SDN Brebeg 01 Jeruklegi - Fajar Solikhin (Universitas Sebelas Maret, 2020)
This article describes efforts to improve mathematics learning achievement through the make a match learning model for grade III students of SD Negeri Brebeg 01 in the 2020/2021 learning year. This study uses two cycles. Where each cycle begins with planning, implementing, observing, and reflecting. The results of this study were that in cycle 1 there was an increase in pre-cycle, 65.52% of students completed and in cycle 2 there was an increase from cycle 1, 86.94% of students completed from 23 students. These results indicate that the make a match learning model can improve student achievement in determining the place value of a number in class III SD Negeri Brebeg 01.